Land sparing outperforms land sharing across an elevational gradient in tropical cattle-farming landscapes - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; James. J. Gilroy; David P. Edwards (Biological Conservation, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Strong Variation in Land‐Use Change Impacts on Tropical Avian Phylogenetic Diversity Between Ecoregions Highlights the Need to Sample Large Spatial Scales - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Robert P. Freckleton; Torbjørn Haugaasen; James J. Gilroy; David P. Edwards (Global Change Biology, 2026)
Forest conversion for agriculture is a major cause of tropical biodiversity loss, but its impacts vary with spatial scale. Higher species turnover in forests than in farmland means that land‐use change causes greater biodiversity loss at broader than at local scales, yet broad‐scale assessments are scarce. Phylogenetic diversity is increasingly prioritised in conservation to protect evolutionary history under global change, yet how deforestation‐driven changes in phylogenetic diversity scale spatially and accumulate in regions of high species turnover remains unclear. We compiled a large field database from across 13 biogeographically diverse regions affected by deforestation for cattle farming, covering most of Colombia, a megadiverse tropical country. Using occupancy models, we estimated bird communities for 1547 (936 observed plus 611 never‐observed) species across ecoregions and nationally in both forest and pasture habitats to quantify changes in phylogenetic diversity metrics and determine whether these impacts are dependent on spatial scale. We found an average loss of 2300 Myr of phylogenetic diversity at the country scale, with most species negatively affected across the phylogeny. Although single regional‐scale relative loss was on average comparable to broader scales, there was high variability between regional units. The latter was especially critical when evaluating metrics of evolutionary distinctiveness, which are key indicators for biodiversity conservation planning. Such underestimation of national‐scale impacts highlights the importance of sampling across multiple regions. Immediate conservation action is needed to safeguard evolutionarily unique species and prevent phylogenetic homogenisation driven by agricultural expansion across spatial scales—a threat often underestimated due to assessments limited to single biogeographic regions.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Consequences of Local Conspecific Density Effects for Plant Diversity and Community Dynamics - Joseph A. LaManna; Florian Hartig; Jonathan A. Myers; Robert P. Freckleton; Matteo Detto; Akshay Surendra; Cole J. Doolittle; Bénédicte Bachelot; Robert Bagchi; Liza S. Comita; David M. DeFilippis; Nohemi Huanca‐Nunez; et al. (Ecology Letters, 2024)
Conspecific density dependence (CDD) in plant populations is widespread, most likely caused by local‐scale biotic interactions, and has potentially important implications for biodiversity, community composition, and ecosystem processes. However, progress in this important area of ecology has been hindered by differing viewpoints on CDD across subfields in ecology, lack of synthesis across CDD‐related frameworks, and misunderstandings about how empirical measurements of local CDD fit within the context of broader ecological theories on community assembly and diversity maintenance. Here, we propose a conceptual synthesis of local‐scale CDD and its causes, including species‐specific antagonistic and mutualistic interactions. First, we compare and clarify different uses of CDD and related concepts across subfields within ecology. We suggest the use of local stabilizing/destabilizing CDD to refer to the scenario where local conspecific density effects are more negative/positive than heterospecific effects. Second, we discuss different mechanisms for local stabilizing and destabilizing CDD, how those mechanisms are interrelated, and how they cut across several fields of study within ecology. Third, we place local stabilizing/destabilizing CDD within the context of broader ecological theories and discuss implications and challenges related to scaling up the effects of local CDD on populations, communities, and metacommunities. The ultimate goal of this synthesis is to provide a conceptual roadmap for researchers studying local CDD and its implications for population and community dynamics.

Pre‐Copulatory Sexual Selection Predicts Sexual Size Dimorphism: A Meta‐Analysis of Comparative Studies - Lennart Winkler; Robert P. Freckleton; Tamás Székely; Tim Janicke (Ecology Letters, 2024)
Size differences between males and females are common across the tree of life (termed sexual size dimorphism; SSD), and have fundamental implications for ecology, life history and behaviour of both sexes. Conventionally, SSD is thought to evolve in response to sex‐specific sexual selection but more recent work suggests that ecological processes can also promote sex‐differences in size. Here, we provide a global test for the role of sexual selection in the evolution of sexual size dimorphism using data from 77 comparative studies spanning the major classes of the animal kingdom. We show that intense sexual selection typically correlates with male‐biased SSD across species. Importantly, pre‐copulatory but not post‐copulatory sexual selection predicts SSD, suggesting a pervasive role of premating male–male competition and female choice to drive sex differences in body size. Collectively, our findings suggest that pre‐copulatory sexual selection plays a major role in the evolution of male‐biased SSD.

Transformation of natural habitat disrupts biogeographical patterns of orchid diversity - Edicson Parra-Sanchez; Robert P. Freckleton; Matthew G. Hethcoat; Jose Manuel Ochoa-Quintero; David P. Edwards (Biological Conservation, 2024)

Tree diversity and liana infestation predict acoustic diversity in logged tropical forests - Zachary Chu; Cindy C.P. Cosset; Catherine Finlayson; Patrick G. Cannon; Robert P. Freckleton; Kalsum M. Yusah; David P. Edwards (Biological Conservation, 2024)

Evolutionary history and climate co‐determine the geographical variation in pollination modes of angiosperms in China - Yunyun Wang; Yichun Li; Ao Luo; Tong Lyu; Robert P. Freckleton; Dimitar Dimitrov; Zhiheng Wang (Global Ecology and Biogeography, 2023)
Aim Pollination is an essential stage of angiosperm reproduction, and the mode of pollination plays a major role in driving evolutionary and ecological responses of plants to environmental changes. However, the effects of climate, evolutionary history and floral traits (i.e. plant sexual systems) on pollination mode variation remain unclear. Here, we explored the biogeographic patterns in pollination mode frequency and tested the hypothesis that insect pollination prevails in warm humid regions with old floras due to high pollinator dependence, whereas wind pollination is more frequent in arid regions with younger floras and is more strongly associated with dioecy. Location China. Time period Since the Last Glacial Maximum. Major taxa studied Angiosperms. Methods Using data on pollination modes and geographic ranges of 29,719 angiosperm species in China, we mapped the biogeographic pattern of pollination mode frequency. Phylogenetic logistic regressions and generalized linear mixed models were employed to evaluate the relative importance of climate, evolutionary history (represented by phylogenetic conservatism and grid‐level mean genus age) and sexual systems on variations in pollination modes across species and space. Results Evolutionary history was the strongest correlate of pollination mode variation across species and space. The proportion of insect‐pollinated species was higher in humid regions with old floras, but lower in arid regions with young floras. Evolutionary history and temperature dominated variations in pollination mode frequency in humid areas, while precipitation dominated in arid areas. Climate influenced geographic pattern in pollination mode frequency both directly and indirectly via its effects on species richness and plant sexual systems. Main Conclusions Our results showed that geographic pattern in angiosperm pollination mode frequency is dominated by evolutionary history followed by climate, which extended previous findings of climate‐driven mechanisms. Our findings demonstrate the importance to incorporate evolutionary history in understanding the mechanisms underlying the functional biogeography of plant traits.

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.

Effects of density, species interactions, and environmental stochasticity on the dynamics of British bird communities - Lisa Sandal; Vidar Grøtan; Bernt‐Erik Sæther; Robert P. Freckleton; David G. Noble; Otso Ovaskainen (Ecology, 2022)
Our knowledge of the factors affecting species abundances is mainly based on time‐series analyses of a few well‐studied species at single or few localities, but we know little about whether results from such analyses can be extrapolated to the community level. We apply a joint species distribution model to long‐term time‐series data on British bird communities to examine the relative contribution of intra‐ and interspecific density dependence at different spatial scales, as well as the influence of environmental stochasticity, to spatiotemporal interspecific variation in abundance. Intraspecific density dependence has the major structuring effect on these bird communities. In addition, environmental fluctuations affect spatiotemporal differences in abundance. In contrast, species interactions had a minor impact on variation in abundance. Thus, important drivers of single‐species dynamics are also strongly affecting dynamics of communities in time and space.

Global distribution and evolutionary transitions of angiosperm sexual systems - Yunyun Wang; Ao Luo; Tong Lyu; Dimitar Dimitrov; Xiaoting Xu; Robert P. Freckleton; Yaoqi Li; Xiangyan Su; Yichao Li; Yunpeng Liu; Denis Sandanov; Qingjun Li; et al. (Ecology Letters, 2021)
Angiosperm sexual systems are fundamental to the evolution and distribution of plant diversity, yet spatiotemporal patterns in angiosperm sexual systems and their drivers remain poorly known. Using data on sexual systems and distributions of 68453 angiosperm species, we present the first global maps of sexual system frequencies and evaluate sexual system evolution during the Cenozoic. Frequencies of dioecy and monoecy increase with latitude, while hermaphrodites are more frequent in warm and arid regions. Transitions to dioecy from other states were higher than to hermaphroditism, but transitions away from dioecy increased since the Cenozoic, suggesting that dioecy is not an evolutionary end point. Transitions between hermaphroditism and dioecy increased, while transitions to monoecy decreased with paleo‐temperature when paleo‐temperature >0℃. Our study demonstrates the biogeography of angiosperm sexual systems from a macroecological perspective, and enhances our understanding of plant diversity patterns and their response to climate change.

Climate and mating systems as drivers of global diversity of parental care in frogs - Balázs Vági; Zsolt Végvári; András Liker; Robert P. Freckleton; Tamás Székely (Global Ecology and Biogeography, 2020)
Aim Amphibians exhibit unusually diverse reproductive modes, including a wide array of parental care strategies. The evolutionary drivers of this diversity, however, remain unclear. Here, we investigate three major factors that might predict interspecific variation in parental care strategies: climate, intrasexual selection and social environment. We hypothesize that some forms of care evolved to cope with harsh conditions, such as dry or unpredictable habitats. We contrast this prediction with the hypothesis that parental roles have co‐evolved with the social environment and mating systems. Location Global. Major taxa studied Frogs and toads (Amphibia: Anura). Time period Extant taxa that represent c . 220 Myr of evolutionary history. Methods Using geographical and behavioural data for 971 species of frogs and toads that represent 45 anuran families, we quantified the global distribution of four forms of parenting separately for males and females: nest building, nest and/or tadpole attendance, carrying and nourishment. We used phylogenetic comparative analyses to investigate whether climate, social environment and mating systems predicted interspecific variation in parental care. Results Our results showed that climatic effects contribute to parental care diversity: in cool and humid climates the males provide offspring attendance, whereas in predictable temperatures endotrophy occurs, whereby the female provides all nutrients for the offspring until metamorphosis. In addition, we found other associations between mating systems and forms of parental care: uniparental clutch attendance by males is present in species with territorial defence, whereas cooperative nest building co‐occurs with sperm competition. The type of parental care is not associated with adult sex ratios. Main conclusions No specific form of care is associated with hostile environments; in fact, some forms of care occur in beneficial conditions, whereas others are used independently from the climate. Instead, parenting diversity has co‐evolved closely with mating systems in frogs.

Drivers of large‐scale geographical variation in sexual systems of woody plants - Yunyun Wang; Tong Lyu; Nawal Shrestha; Lisha Lyu; Yaoqi Li; Bernhard Schmid; Robert P. Freckleton; Dimitar Dimitrov; Shuguang Liu; Zhanqing Hao; Zhiheng Wang (Global Ecology and Biogeography, 2020)
Aim Sexual systems strongly influence angiosperm evolution and play important roles in community assembly and species responses to climate change. However, geographical variation in proportions of different sexual systems (dioecy, monoecy and hermaphroditism) in response to changes in climate, life‐history traits and evolutionary age remains poorly understood. Here, we map the geographical variation in proportions of different sexual systems and hypothesize that the prevalence of hermaphrodites increases with aridity owing to their advantages in colonizing harsh environments, whereas dioecy is most successful in humid regions with tall‐canopy vegetation and old floras. Location China. Time period Current. Major taxa studied Woody angiosperms. Methods Using data on sexual systems and distributions of 10,449 woody species in China, we estimated the proportions of different sexual systems in local floras (50 km × 50 km grid cells). Spatial linear models, phylogenetic general linear models and structural equation models were used to compare the relative influences of climate, plant height and evolutionary age on geographical variation in proportions of different sexual systems. Results We found contrasting geographical patterns in the proportions of different sexual systems. The proportions of dioecy and monoecy increased with plant height and were highest in humid regions with older floras, whereas that of hermaphroditism decreased with plant height and was highest in arid regions with younger floras. Plant height was the strongest correlate of sexual system frequency. Climate influenced sexual system frequency both directly and indirectly via its effects on plant height. Main conclusions Our study provides the first continuous map of sexual system composition in woody floras over a large spatial scale. Our findings suggest that mature plant height, reflecting plant longevity, dominates geographical variation in sexual systems and that the proportions of different sexual systems in local floras might reflect their correlated evolution with traits in response to climate changes.

Phylogeny and ecological processes influence grass coexistence at different spatial scales within the steppe biome - Hui Liu; Colin P. Osborne; Deyi Yin; Robert P. Freckleton; Gaoming Jiang; Meizhen Liu (Oecologia, 2019)

Uncovering the spatio‐temporal drivers of species trait variances: a case study of Magnoliaceae in China - Hui Liu; Marjorie R. Lundgren; Robert P. Freckleton; Qiuyuan Xu; Qing Ye (Journal of Biogeography, 2016)
Aim Analyses of the relationships between evolutionary history, environmental constraints and associated trait variances can reveal how species distributions were shaped. Phylogenetic comparative models can be used to disentangle the relative roles of spatial and phylogenetic factors in explaining trait variances. Here, we analyse variances in plant traits and environmental variables of the widely distributed and early diverging Magnoliaceae within a phylogeographical context to test whether species distributions have been limited more by evolutionary or spatial constraints in this family. Location China. Methods The phylogenetic relatedness and geographical distributions of 183 Magnoliaceae species in China were analysed for phylogenetic clustering or over‐dispersion. The phylogenetic signals of 15 plant traits and 12 environmental variables were determined, and the relative contributions of phylogeny and space to each quantitative trait were distinguished using four comparative models. Results Species richness gradually decreased from south to north, with phylogenetic clustering along the southern coast, and in northern and central China. Strong phylogenetic signals were found in leaf form, flowering sequence, diameter at breast height, leaf length and width, mean and minimum mean annual temperature, and minimum mean annual precipitation. Variances of plant diameter, length and width of leaves and tepals, and fruit length were strongly associated with phylogenetic relatedness. In contrast, variances of plant height, flowering and fruiting time, and all of the 12 environmental variables (mean, minimum, maximum and range of altitude, temperature and precipitation) were associated with both spatial proximity and phylogenetic distance between species. Main conclusions Phylogenetic niche conservatism was identified in most of the studied plant traits across the Magnoliaceae. In contrast, environmental variables showed weak phylogenetic signals, but strong spatial signals. These results suggest that the present tropical‐temperate distributional pattern of the Magnoliaceae is driven by the ecophysiological adaptation of plant traits under both geographical separation and environmental constraints.

Phylogenetic constraints and trait correlates of flowering phenology in the angiosperm flora of C hina - Yanjun Du; Lingfeng Mao; Simon A. Queenborough; Robert P. Freckleton; Bin Chen; Keping Ma (Global Ecology and Biogeography, 2015)
Aim The phylogenetic constraint hypothesis of flowering phenology states that closely related species flower at similar times of the year. We test this hypothesis for the C hinese angiosperm flora and assess additional effects of growth form, deciduousness, pollination mode and fruit type. We further examine whether the phylogenetic conservatism of flowering phenology tends to increase from tropical to temperate latitudes. Location C hina. Methods The midpoint of flowering time for 19,631 angiosperm species present in C hina was compiled. The phylogenetic signal for flowering time was evaluated for the whole country using the B lomberg K ‐value (adjusted for circular data). We then regressed the phylogenetic signal for 28 provinces as a function of their latitude. An analysis of variance for circular data was conducted to test the differences among growth forms. W atson– W illiams tests for circular flowering data were used to compare flowering dates between deciduous and evergreen species, animal‐pollinated and wind‐pollinated species, and fleshy and non‐fleshy fruits. Results The results support the phylogenetic constraint hypothesis. The phylogenetic signal at the whole country scale was lower than that at the province scale. Phylogenetic signal was also lower at tropical latitudes than at temperate latitudes. Flowering dates were associated with biological traits, with growth form having the largest effect. Main conclusions Flowering phenology was constrained by phylogeny, and so one should account for phylogeny when studying the underlying drivers of phenology. The strength of phylogenetic conservatism appears weaker at larger scales and becomes stronger towards temperate regions. Flowering phenology also varies predictably according to biological traits such as growth form, suggesting that both phylogeny and traits could be used to inform the flowering times of species for which no phenology data are available. It remains to be tested whether the phylogenetic signal for other functional traits putatively related with flowering time also increases with latitude.

Mechanisms driving an unusual latitudinal diversity gradient for grasses - Vernon Visser; W. Derek Clayton; David A. Simpson; Robert P. Freckleton; Colin P. Osborne (Global Ecology and Biogeography, 2014)
Aim For most higher‐order taxa, species diversity peaks sharply in the moist tropics and declines rapidly at higher latitudes. However, the mechanisms driving this latitudinal gradient are numerous, remain uncertain and are even undocumented in some important major clades such as the grasses. Grasses are a cosmopolitan, important plant family with more than 11,000 species world‐wide. Our aims were: to investigate the latitudinal distributions of species richness for different grass lineages, and the grass family as a whole; and to test hypotheses proposed in general for the latitudinal diversity gradient or specifically as determinants of grass species richness patterns at the global scale. Location Global. Methods We used the most comprehensive global database of grass distributions currently available to calculate species richness for 340 political regions of the world. Using generalized additive models we used these data to model the latitudinal gradients of species richness for different grass lineages and for the grass family as a whole. We constructed multiple regression models to include climatic, productivity, topographic, habitat and geographic variables. Results An unusual, shallow latitudinal diversity gradient arises because different grass lineages exhibit contrasting latitudinal patterns. This reflects differential specialization of grass lineages to arid and cool environments, the legacy of historical effects, most notably the Gondwanan origin of the grasses, and a strong association between grasses and topographically heterogeneous, mountainous regions. Main conclusions The grasses are one of the relatively few higher‐order lineages that exhibits an atypical latitudinal gradient; this has arisen because of climatic specialization of particular grass lineages to cold and arid environments. Key additional roles have been inferred for historical biogeography and topographical heterogeneity in determining global patterns of grass species richness. These mechanisms have generally been under‐appreciated and are probably important for many other lineages.

Phylogenetic niche conservatism in C4 grasses - Hui Liu; Erika J. Edwards; Robert P. Freckleton; Colin P. Osborne (Oecologia, 2012)

Characterizing abundance–occupancy relationships: there is no artefact - Thomas J. Webb; Robert P. Freckleton; Kevin J. Gaston (Global Ecology and Biogeography, 2012)
Positive abundance–occupancy relationships (AORs) are among the most general macroecological patterns: locally common species are regionally widespread, locally rare species are regionally restricted. In a recent contribution, Wilson ( Global Ecology and Biogeography , 2011, 20 , 193–202) made three claims: (1) that AORs are critically dependent on the method used to calculate average abundance; (2) averaging abundance over occupied sites tends to lead to a very high incidence of negative relationships; (3) this represents a statistical artefact that should be considered in studies of AORs. Here we show that this outcome arises in Wilson's simulations purely due to an arbitrary choice of occupancy models and parameter ranges. The resulting negative relationships are not statistical artefacts, but are easily interpreted in terms of spatial aggregation in abundant species. The fact that empirical evidence fails to support a high prevalence of negative AORs suggests, however, that such parameter combinations arise only rarely in nature. We conclude that simulations that are based on untested assumptions, and that produce patterns unsupported by empirical evidence, have limited use in characterizing AORs, and add little to understanding of the processes driving important relationships between local population size and regional occupancy.

Dealing with collinearity in behavioural and ecological data: model averaging and the problems of measurement error - Robert P. Freckleton (Behavioral Ecology and Sociobiology, 2011)

Model averaging, missing data and multiple imputation: a case study for behavioural ecology - Shinichi Nakagawa; Robert P. Freckleton (Behavioral Ecology and Sociobiology, 2011)

Testing the Janzen‐Connell mechanism: pathogens cause overcompensating density dependence in a tropical tree - Robert Bagchi; Tom Swinfield; Rachel E. Gallery; Owen T. Lewis; Sofia Gripenberg; Lakshmi Narayan; Robert P. Freckleton (Ecology Letters, 2010)
Ecology Letters (2010) Abstract The Janzen‐Connell hypothesis is a leading explanation for plant‐species diversity in tropical forests. It suggests that specialized natural enemies decrease offspring survival at high densities beneath parents, giving locally rarer species an advantage. This mechanism, in its original form, assumes that density dependence is overcompensating: mortality must be disproportionately high at the highest densities, with few offspring recruiting below their parents. We tested this assumption using parallel shadehouse and field density‐series experiments on seedlings of a tropical tree, Pleradenophora longicuspis . We found strong, overcompensating mortality driven by fungal pathogens, causing 90% (shadehouse) or 100% (field) mortality within 4 weeks of germination, and generating a negative relationship between initial and final seedling densities. Fungicide treatment led to much lower, density‐independent, mortality. Overcompensating mortality was extremely rapid, and could be missed without detailed monitoring. Such dynamics may prevent dead trees from being replaced by conspecifics, promoting coexistence as envisioned by the Janzen‐Connell hypothesis.

Niches versus neutrality: uncovering the drivers of diversity in a species‐rich community - Remi Vergnon; Nicholas K. Dulvy; Robert P. Freckleton (Ecology Letters, 2009)
Ecological models suggest that high diversity can be generated by purely niche‐based, purely neutral or by a mixture of niche‐based and neutral ecological processes. Here, we compare the degree to which four contrasting hypotheses for coexistence, ranging from niche‐based to neutral, explain species richness along a body mass niche axis. We derive predictions from these hypotheses and confront them with species body‐mass patterns in a highly sampled marine phytoplankton community. We find that these patterns are consistent only with a mechanism that combines niche and neutral processes, such as the emergent neutrality mechanism. In this work, we provide the first empirical evidence that a niche‐neutral model can explain niche space occupancy pattern in a natural species‐rich community. We suggest this class of model may be a useful hypothesis for the generation and maintenance of species diversity in other size‐structured communities.

Should conservation strategies consider spatial generality? Farmland birds show regional not national patterns of habitat association - Mark J. Whittingham; John R. Krebs; Ruth D. Swetnam; Juliet A. Vickery; Jeremy D. Wilson; Robert P. Freckleton (Ecology Letters, 2007)
A key assumption underlying any management practice implemented to aid wildlife conservation is that it will have similar effects on target species across the range it is applied. However, this basic assumption is rarely tested. We show that predictors [nearly all associated with agri‐environment scheme (AES) options known to affect European birds] had similar effects for 11 bird species on sites with differing farming practice (pastoral vs. mixed farming) or which differed in the density at which the species was found. However, predictors from sites in one geographical region tended to have different effects in other areas suggesting that AES options targeted at a regional scale are more likely to yield beneficial results for farmland birds than options applied uniformly in national schemes. Our study has broad implications for designing conservation strategies at an appropriate scale, which we discuss.

Plant pathogens drive density‐dependent seedling mortality in a tropical tree - Thomas Bell; Robert P. Freckleton; Owen T. Lewis (Ecology Letters, 2006)
One explanation for the extraordinary diversity of tropical forest trees is that density‐dependent mortality from herbivores or pathogens puts locally rare species at an advantage. Density‐dependent mortality of seeds and small seedlings is particularly intense in tropical forests, but its causes remain uncertain. Here, we show experimentally that pathogens from the Oomycota are associated with intense mortality in seedlings of a neotropical tree, Sebastiana longicuspis . Seedlings in untreated plots experienced eight times higher mortality compared with seedlings in plots treated with fungicide. Mortality was strongly density dependent: in fungicide‐treated plots survival was unaffected by density, but survival in unsprayed plots was over three times higher at low density. Density‐dependent mortality observed in a simultaneous, non‐manipulative study was highly transient, suggesting that short‐term observational studies may underestimate the intensity and form of pathogen‐induced mortality. If such effects are widespread, plant pathogens may play a key role in maintaining and structuring tropical diversity.

Seeing the jungle for the trees - Robert P. Freckleton (Journal of Biogeography, 2004)

Coral reef cascades and the indirect effects of predator removal by exploitation - Nicholas K. Dulvy; Robert P. Freckleton; Nicholas V. C. Polunin (Ecology Letters, 2004)
Fisheries exploitation provides the opportunity to examine the ecosystem‐scale biodiversity consequences of predator removal. We document predatory reef fish densities, coral‐eating starfish densities and coral reef structure along a 13‐island gradient of subsistence exploitation in Fiji. Along the fishing intensity gradient, predator densities declined by 61% and starfish densities increased by three orders of magnitude. Reef‐building corals and coralline algae declined by 35% and were replaced by non‐reef building taxa (mainly filamentous algae), as a result of starfish predation. Starfish populations exhibited thresholds and Allee‐type dynamics: population growth was negative under light fishing intensities and high predator densities, and positive on islands with higher fishing intensities and low predator densities. These results suggest the depletion of functionally important consumer species by exploitation can indirectly influence coral reef ecosystem structure and function at the scale of islands.